DESIGN ANALYSIS OF A LOW-COST PARABOLIC ANTENNA FOR DEVELOPING NATION - FRANK ONAIFO; ALEXANDER AKPOFURE OKANDEJI; FISAYO IDOWU; OMOWUMMI GRACE OLASUNKANMI; OLAWALE OLALUWOYE; OLAOLU FOLORUNSHO (Journal of Engineering Studies and Research)
This paper is aimed at designing a locally fabricated fiberglass parabolic antenna as a replacement for a metallic fabricated parabolic antenna. They are coated with a thin film of aluminum dust to enhance reflectivity since electromagnetic radiations do not travel deep in a conductor. This reduces the thick mass of metal usually used for constructing metallic parabolic antenna leading to a reduced cost of production. It incorporates a Low Noise Block (LNB) Converter comprising of amplifiers and frequency down converter. Metallic parabolic antenna contributes more to signal loss by reflecting radio waves. The Parabolic antenna is designed to receive microwave signals in the K-band with the down converter converting it to very high frequency (VHF) and ultra-high frequency (UHF) employing the super-heterodyning principle. The study shows the design and installation of a low-cost parabolic antenna in the rural community in Nigeria. The designed parabolic antenna is used to receive a signal with the center frequency of 11.3GHz and signal strength of 60%. The economic viability is that fiber-glass Parabolic antenna can replace the metallic fabricated ones.